Food for Thought: Rido’s Culinary-Inspired Platform Branding in Jakarta’s 2024 Gubernatorial Campaign - Lolita, Theresia Lavietha Vivrie (ARISTO, 2024)
This study examines the innovative culinary-inspired policy branding strategy employed by the Ridwan Kamil-Suswono (RIDO) campaign in Jakarta’s 2024 gubernatorial race. Using food-related acronyms for their flagship programs, RIDO aimed to make complex policy ideas more accessible and memorable to Jakarta’s voters. The study analyzes eight creative program names, each forming an acronym of a popular Indonesian dish, designed to capture attention and create positive associations with RIDO’s policy agenda. This approach simplifies policy communication and fosters a sense of local pride and cultural identity. The study explores how this strategy reflects an understanding of Jakarta’s multicultural fabric and may help the campaign appeal to diverse communities. Furthermore, it investigates how this culinary branding serves as a unique form of political communication, potentially increasing voter engagement and recall of key campaign promises. The study considers the effectiveness of this approach in the context of Jakarta’s reputation as a culinary hub and evaluates its potential impact on voter perceptions and campaign success.